Chinglish: Unraveling the Cultural and Cognitive Pattern Differences in Cross-Linguistic Communication - Xiaofang Zhao; Esther Jawing; Xiaoman Liu (Secholian Publication (Kuala Lumpur, Malaysia), 2023)
English, as a foreign language in China, is often influenced by the first language (L1), which is Chinese, giving rise to the phenomenon of Chinglish. Chinglish, a distinct English variety, significantly differs from standard English in various aspects. The prominent reason for these differences lies in the variance of culture and thinking patterns. Unfortunately, Chinglish impedes effective cross-cultural communication and hinders the advancement of English learners’ proficiency. This study aims to elucidate the current state and specific manifestations of Chinglish concerning vocabulary and syntax from the perspective of cultural and cognitive disparities. The research employs questionnaire surveys and material analysis methods to gather data. Preliminary analysis reveals the widespread prevalence of Chinglish during the English learning process, with the primary vocabulary errors being redundancy, improper word usage, and incorrect collocation. In terms of syntax, word order, tense, and voice are particularly discussed as problematic areas. This paper concludes with suggestions for avoiding Chinglish, aiming to enhance cross-cultural communication and elevate English proficiency levels among Chinese learners.